All-solid battery

By optimizing the structure of the positive electrode active material layer in an all-solid-state battery and adopting a combination design of single-particles and polycrystalline particles, the shortcomings in the rate and cycle characteristics of the all-solid-state battery are solved, and better battery performance is achieved.

JP2025018622APending Publication Date: 2025-02-06NISSAN MOTOR CO LTD

Patent Information

Application Number
JP2023122498
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The existing all-solid-state batteries have shortcomings in taking into account both the rate characteristics and the cycle characteristics.

Method used

In the positive electrode active material layer of an all-solid state battery, a single-particle positive electrode active material is placed on the surface facing the solid electrolyte layer, while a polycrystalline positive electrode active material is placed on the surface facing the positive current collector, and the single particle ratio is controlled to form a specific layer structure.

Benefits of technology

It realizes the balance of rate characteristics and cycle characteristics of all-solid-state batteries, and improves the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018622000003
    Figure 2025018622000003
  • Figure 2025018622000004
    Figure 2025018622000004
  • Figure 2025018622000001
    Figure 2025018622000001
Patent Text Reader

Abstract

To provide means for achieving both rate characteristics and cycle characteristics in an all-solid battery.SOLUTION: An all-solid battery includes a power generating element having a positive electrode in which a positive electrode active material layer containing a positive electrode active material is disposed on a surface of a positive electrode current collector, a negative electrode, and a solid electrolyte layer containing a solid electrolyte and interposed between the positive electrode and the negative electrode, and in the positive electrode active material layer, a single particle ratio R1 (volume %) which is the ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a first surface layer that is 20% thick from the surface of the surface facing the solid electrolyte layer is greater than a single particle ratio R2 (volume %) which is the ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a second surface layer that is 20% thick from the surface of the surface facing the positive electrode current collector.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery. [Background technology]

[0002] In recent years, research and development of all-solid-state batteries, such as all-solid-state lithium secondary batteries that use oxide- or sulfide-based solid electrolytes, has been actively conducted. A solid electrolyte is a material that is mainly composed of an ion conductor that can conduct lithium ions in a solid state. Therefore, all-solid-state batteries have the advantage that, in principle, various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium secondary batteries, do not occur.

[0003] Here, Patent Document 1 describes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The document discloses a positive electrode composite layer having a ratio of electronic conductivity to Li-ion conductivity of 0.39 or less, the positive electrode composite layer having a solid electrolyte material containing O2, Li, P, and S elements, and VGCF (vapor grown carbon fiber) as a conductive additive. According to the document, the rapid charging capacity of the all-solid-state battery can be improved by adopting such a configuration. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6314563 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the inventors have conducted studies and found that all-solid-state batteries using the techniques described in the above documents may not be able to achieve both rate characteristics and cycle characteristics.

[0006] Therefore, an object of the present invention is to provide a means for achieving both rate characteristics and cycle characteristics in an all-solid-state battery. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by disposing a single-particle positive electrode active material on a surface layer facing a solid electrolyte layer and a polycrystalline positive electrode active material on a surface layer facing a positive electrode current collector in a positive electrode active material layer of an all-solid-state battery, thereby completing the present invention.

[0008] That is, one embodiment of the present invention relates to an all-solid-state battery including a power generating element including a positive electrode in which a positive electrode active material layer containing a positive electrode active material is disposed on the surface of a positive electrode current collector, a negative electrode, and a solid electrolyte layer containing a solid electrolyte interposed between the positive electrode and the negative electrode. The all-solid-state battery is characterized in that, in the positive electrode active material layer, a single particle ratio R1 (volume %), which is a ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a first surface layer up to 20% of the thickness from the surface of the surface facing the solid electrolyte layer, is larger than a single particle ratio R2 (volume %), which is a ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a second surface layer up to 20% of the thickness from the surface of the surface facing the positive electrode current collector. Effect of the Invention

[0009] According to the present invention, an all-solid-state battery that achieves both rate characteristics and cycle characteristics is provided. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing the appearance of a flat laminate-type all-solid-state lithium secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] One embodiment of the present invention is an all-solid-state battery including a power generating element having a positive electrode in which a positive electrode active material layer containing a positive electrode active material is disposed on the surface of a positive electrode current collector, a negative electrode, and a solid electrolyte layer containing a solid electrolyte interposed between the positive electrode and the negative electrode, wherein in the positive electrode active material layer, a single particle ratio R1 (volume %) which is the ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a first surface layer up to 20% of the thickness from the surface of the surface facing the solid electrolyte layer is larger than a single particle ratio R2 (volume %) which is the ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a second surface layer up to 20% of the thickness from the surface of the surface facing the positive electrode current collector. According to this embodiment, an all-solid-state battery that achieves both rate characteristics and cycle characteristics is provided.

[0012] Hereinafter, the present embodiment will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the claims and is not limited to the following embodiments. The dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios. In this specification, the range "X to Y" means "X or more and Y or less." Furthermore, unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50% RH.

[0013] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state lithium secondary battery according to one embodiment of the present invention. FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. 1. The laminated type allows the battery to be compact and have a high capacity. In this specification, the flat laminated type non-bipolar all-solid-state lithium secondary battery (hereinafter also simply referred to as a "laminated type secondary battery") shown in FIG. 1 and FIG. 2 will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the secondary battery according to this embodiment, it can be applied to both non-bipolar type (internal parallel connection type) batteries and bipolar type (internal series connection type) batteries.

[0014] As shown in Fig. 1, the stacked secondary battery 10a has a flat rectangular shape, and a negative electrode current collector 25 and a positive electrode current collector 27 for extracting electric power are drawn out from both sides of the stacked secondary battery 10a. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked secondary battery 10a, and the periphery is heat-sealed, and the power generating element 21 is sealed in a state in which the negative electrode current collector 25 and the positive electrode current collector 27 are drawn out to the outside. Note that the drawing out of the current collectors (25, 27) shown in Fig. 1 is not limited to that shown in Fig. 1, and the negative electrode current collector 25 and the positive electrode current collector 27 may be drawn out from the same side, or the negative electrode current collector 25 and the positive electrode current collector 27 may each be divided into a plurality of pieces and drawn out from each side.

[0015] As shown in FIG. 2, the power generating element 21 of the stacked secondary battery 10a of this embodiment has a configuration in which, during charging, a negative electrode in which a negative electrode active material layer 13 made of lithium metal is arranged on both sides of a negative electrode collector 11′, a solid electrolyte layer 17, and a positive electrode in which a positive electrode active material layer 15 containing a lithium transition metal composite oxide is arranged on both sides of a positive electrode collector 11″ are stacked. Specifically, the negative electrode, the solid electrolyte layer, and the positive electrode are stacked in this order such that one negative electrode active material layer 13 and an adjacent positive electrode active material layer 15 face each other with the solid electrolyte layer 17 interposed therebetween. As a result, the adjacent negative electrode, solid electrolyte layer, and positive electrode constitute one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 2 can also be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.

[0016] A negative current collector 25 and a positive current collector 27 which are electrically connected to the electrodes (negative and positive) are attached to the negative current collector 11' and the positive current collector 11", respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The negative current collector 25 and the positive current collector 27 may be attached to the negative current collector 11' and the positive current collector 11" of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a negative terminal lead and a positive terminal lead (not shown) as necessary.

[0017] In the stacked secondary battery 10a according to this embodiment, the power generating element 21 sealed in the laminate film 29 shown in FIG. 1 and the power generating element 21 sealed in the laminate film 29 are preferably sandwiched between two plate-like members and further fastened using a fastening member. As a result, the plate-like member and the fastening member function as a pressure member that presses (restrains) the power generating element 21 in its stacking direction. Examples of the plate-like member include a metal plate and a resin plate. Examples of the fastening member include a bolt and a nut. However, the pressure member is not particularly limited as long as it is a member that can pressurize the power generating element 21 in its stacking direction. As the pressure member, a combination of a plate made of a material having rigidity like the plate-like member and the above-mentioned fastening member is typically used. Also, as for the fastening member, not only bolts and nuts but also tension plates that fix the ends of the plate-like members so as to restrain the power generating element 21 in its stacking direction may be used. The lower limit of the load applied to the power generating element 21 (restraint pressure in the stacking direction of the power generating element) is, for example, 0.1 MPa or more, preferably 1 MPa or more, more preferably 3 MPa or more, and even more preferably 5 MPa or more. The upper limit of the restraint pressure in the stacking direction of the power generating element is, for example, 100 MPa or less, preferably 70 MPa or less, more preferably 40 MPa or less, and even more preferably 10 MPa or less.

[0018] The main components of the above-mentioned stacked secondary battery 10a will now be described.

[0019] [Current collector] The current collectors (negative electrode current collector 11′ and positive electrode current collector 11”) are conductive members that function as paths for electrons flowing in and out of the battery as the battery reaction (charge / discharge reaction) progresses. There are no particular limitations on the material that constitutes the current collectors, and for example, metals or conductive resins can be used.

[0020] Specifically, examples of metals include aluminum, nickel, iron, stainless steel, titanium, and copper. In addition to these, clad materials of nickel and aluminum, clad materials of copper and aluminum, and the like may be used. Also, foils in which the metal surface is coated with aluminum may be used. Among these, aluminum, stainless steel, copper, and nickel are preferred from the viewpoints of electronic conductivity, battery operating potential, and adhesion of active materials.

[0021] The latter conductive resin may be a conductive polymer material or a non-conductive polymer material to which a conductive filler is added as required.

[0022] The current collector may have a single layer structure made of a single material, or may have a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector contains at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. There is no particular limit to the thickness of the current collector, but an example is 10 to 100 μm.

[0023] [Negative electrode active material layer] The negative electrode active material layer 13 includes a negative electrode active material. The type of the negative electrode active material is not particularly limited, and may include a carbon material, a metal oxide, and a metal active material. In addition, a metal containing lithium may be used as the negative electrode active material. Such a negative electrode active material is not particularly limited as long as it is an active material containing lithium, and may include lithium metal as well as a lithium-containing alloy. Examples of the lithium-containing alloy include an alloy of Li and at least one of In, Al, Si, Sn, Mg, Au, Ag, and Zn. The negative electrode active material preferably includes lithium metal or a lithium-containing alloy, a silicon-based negative electrode active material, or a tin-based negative electrode active material, and more preferably includes lithium metal or a lithium-containing alloy. In addition, when the negative electrode active material uses lithium metal or a lithium-containing alloy, the stacked secondary battery according to this embodiment may be a so-called lithium precipitation type in which lithium metal is precipitated as a negative electrode active material on a negative electrode current collector during charging. Therefore, in such a configuration, the thickness of the negative electrode active material layer increases with the progress of the charging process, and the thickness of the negative electrode active material layer decreases with the progress of the discharging process. The negative electrode active material layer does not need to be present during full discharge, but in some cases, a negative electrode active material layer made of a certain amount of lithium metal may be present during full discharge.

[0024] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably within the range of 40 to 100 mass %, and more preferably within the range of 50 to 90 mass %, for example.

[0025] The negative electrode active material layer may further include a solid electrolyte, if necessary. When the negative electrode active material layer includes a solid electrolyte, the ion conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes. In this specification, the solid electrolyte refers to a material mainly composed of an ion conductor capable of ion conduction in a solid, and in particular, a material having a lithium ion conductivity of 1×10 at room temperature (25° C.) -5 S / cm or more, and this lithium ion conductivity is preferably 1×10 -4It is above S / cm. Here, the value of ionic conductivity can be measured by the AC impedance method.

[0026] The solid electrolyte preferably is a sulfide solid electrolyte containing S element from the viewpoint of exhibiting excellent lithium ion conductivity and being more able to follow the volume change of the electrode active material accompanying charge and discharge. More preferably, it is a sulfide solid electrolyte containing Li element, M element and S element, and the M element contains at least one element selected from the group consisting of P, Si, Ge, Sn, Ti, Zr, Nb, Al, Sb, Br, Cl and I. Even more preferably, it is a sulfide solid electrolyte containing S element, Li element and P element.

[0027] The sulfide solid electrolyte may have a Li3PS4 skeleton, a Li4P2S7 skeleton or a Li4P2S6 skeleton. Examples of the sulfide solid electrolyte having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. Examples of the sulfide solid electrolyte having a Li4P2S7 skeleton include a Li-P-S based solid electrolyte called LPS. Also, as the sulfide solid electrolyte, for example, LGPS represented by Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1) such as LGPS may be used. More specifically, for example, LPS (Li2S-P2S5), Li7P3S 11 、Li 3.2 P 0.96 S、Li 3.25 Ge 0.25 P 0.75 S4、Li 10 GeP2S 12, or Li6PS5X (wherein X is Cl, Br, or I). The term "Li2S-P2S5" refers to a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other terms. Among them, the sulfide solid electrolyte is preferably LPS (Li2S-P2S5), Li6PS5X (wherein X is Cl, Br, or I), Li7P3S, etc., from the viewpoint that it has high ionic conductivity and a low bulk modulus and can follow the volume change of the electrode active material during charging and discharging. 11 , Li 3.2 P 0.96 S and Li3PS4.

[0028] The shape of the solid electrolyte may be, for example, a particulate shape such as a perfect sphere or an oval sphere, or a thin film. When the solid electrolyte is particulate, its average particle size (D50) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. On the other hand, the average particle size (D50) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.

[0029] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.

[0030] The negative electrode active material layer may further contain at least one of a binder and a conductive assistant in addition to the above-mentioned negative electrode active material and solid electrolyte. The thickness of the negative electrode active material layer varies depending on the configuration of the intended secondary battery, but is preferably within a range of, for example, 0.1 to 1000 μm, and more preferably 40 to 100 μm.

[0031] [Solid electrolyte layer] The solid electrolyte layer 17 is interposed between the positive electrode active material layer 15 and the negative electrode active material layer 13, and contains a solid electrolyte (usually as a main component). There is no particular limitation on the specific form of the solid electrolyte contained in the solid electrolyte layer, and the solid electrolytes exemplified in the section on the negative electrode active material layer and their preferred forms can be similarly adopted. In some cases, a solid electrolyte other than the above-mentioned solid electrolytes may be used in combination.

[0032] The content of the solid electrolyte in the solid electrolyte layer is, for example, preferably in the range of 10 to 100 mass%, more preferably in the range of 50 to 100 mass%, and further preferably in the range of 90 to 100 mass%, relative to the total mass of the solid electrolyte layer.

[0033] The solid electrolyte layer may further contain a binder in addition to the above-mentioned solid electrolyte. The thickness of the solid electrolyte layer varies depending on the configuration of the intended secondary battery, but is preferably within a range of, for example, 0.1 to 1000 μm, and more preferably 10 to 40 μm.

[0034] [Cathode active material layer] The positive electrode active material layer 15 includes a positive electrode active material. The type of the positive electrode active material is not particularly limited, but examples thereof include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of metal oxides other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12Among these, composite oxides containing lithium and nickel are preferably used, and more preferably Li(Ni-Mn-Co)O2 and those in which some of these transition metals have been replaced with other elements (hereinafter also simply referred to as "NMC composite oxides"). NMC composite oxides have a layered crystal structure in which lithium atomic layers and transition metal (Mn, Ni, and Co arranged in an orderly manner) atomic layers are alternately stacked with oxygen atomic layers interposed therebetween, and contain one Li atom per transition metal M atom, so that the amount of Li that can be extracted is twice that of spinel-based lithium manganese oxides, i.e., the supply capacity is doubled, and high capacity can be achieved.

[0035] As described above, the NMC composite oxide also includes composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, Zn, etc., preferably Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, more preferably Ti, Zr, P, Al, Mg, Cr, and even more preferably Ti, Zr, Al, Mg, Cr from the viewpoint of improving cycle characteristics.

[0036] Since the NMC composite oxide has a high theoretical discharge capacity, it is preferable to use the NMC composite oxide represented by the general formula (1): Li a Ni b Mn c Co d M xO2 (wherein, in the formula, a, b, c, d, and x satisfy 0.98 ≦ a ≦ 1.2, 0.6 ≦ b ≦ 0.9, 0 < c ≦ 0.4, 0 < d ≦ 0.4, 0 ≦ x ≦ 0.3, and b + c + d + x = 1. M is at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr). Here, a represents the atomic ratio of Li, b represents the atomic ratio of Ni, c represents the atomic ratio of Mn, d represents the atomic ratio of Co, and x represents the atomic ratio of M. Further, in the laminated secondary battery according to this embodiment, the positive electrode active material is preferably an NMC composite oxide (high nickel NMC composite oxide) that satisfies 0.8 ≦ b ≦ 0.9, 0 < c ≦ 0.2, 0 < d ≦ 0.2, and 0 ≦ x ≦ 0.2 in the general formula (1) described above. It is preferable that the atomic ratio b of Ni is 0.8 or more because the balance between capacity and life characteristics is excellent. Also, when the atomic ratio b of Ni is 0.9 or less, the generation of gas accompanying the electrode reaction can be reduced. Therefore, it is preferable because a decrease in cycle durability due to gas generation is less likely to occur. At this time, in the general formula (1), it is more preferable that c and d are 0.05 ≦ c ≦ 0.2 and 0.03 ≦ d ≦ 0.2 from the viewpoint of improving the balance between capacity and life characteristics.

[0037] The stacked secondary battery 10a according to this embodiment is characterized in that in the positive electrode active material layer, the single particle ratio R1 (volume %), which is the ratio of the total volume of the single particles to the total volume of the positive electrode active material contained in the first surface layer from the surface facing the solid electrolyte layer to 20% of the thickness, is larger than the single particle ratio R2 (volume %), which is the ratio of the total volume of the single particles to the total volume of the positive electrode active material contained in the second surface layer from the surface facing the positive electrode current collector to 20% of the thickness. In this specification, the single particle ratios R1 and R2 are values ​​measured by the method described in the examples below. In addition, whether the positive electrode active material is single particle or polycrystalline can be determined by crystal analysis using SEM-EBSD (scanning electron microscope-electron backscattering analysis), as described in the examples below. In this way, when comparing the surface portion of the positive electrode active material layer facing the solid electrolyte layer with the surface portion of the positive electrode active material layer facing the positive electrode current collector, the former has a higher proportion of single-particle positive electrode active material (the latter has a higher proportion of polycrystalline positive electrode active material), so that it is possible to achieve both rate characteristics and cycle characteristics. The present inventors speculate as follows about the mechanism by which such an effect is achieved. Since a polycrystalline positive electrode active material has a larger surface area per unit volume than a single-particle positive electrode active material, it has been conventionally known that by using this in the positive electrode active material layer, the contact area with the solid electrolyte is increased and excellent rate characteristics are exhibited. However, when the present inventors performed a cycle test on an all-solid-state battery having a positive electrode active material layer prepared using a polycrystalline positive electrode active material, it was found that sufficient cycle characteristics were not obtained. When the cross section of the positive electrode active material layer after the cycle test was cut in the thickness direction, it was observed using a scanning electron microscope (SEM) and it was confirmed that many cracks had occurred in the positive electrode active material particles contained in the surface layer of the positive electrode active material layer facing the solid electrolyte layer. It was believed that the occurrence of such cracks would reduce the utilization efficiency of the positive electrode active material and the cycle characteristics. It was also confirmed that the number of cracks decreased from the center part of the positive electrode active material layer in the thickness direction to the surface layer facing the positive electrode current collector.Based on this knowledge, the inventors attempted to suppress the occurrence of cracks by disposing a single particle positive electrode active material on the surface layer facing the solid electrolyte layer. As a result, they found that it was possible to significantly improve cycle characteristics without significantly deteriorating the rate characteristics, and thus completed the present invention. The positive electrode active material shrinks and expands due to the charge and discharge reaction. This shrinkage and expansion makes it easy for cracks to occur in polycrystalline positive electrode active materials, but it is difficult for cracks to occur in single particle positive electrode active materials, so it is believed that the decrease in the utilization efficiency of the positive electrode active material in the surface portion on the side facing the solid electrolyte layer is suppressed, and the cycle characteristics are improved.

[0038] In this embodiment, the values ​​of the single particle ratios R1 and R2 are not particularly limited as long as R1>R2 is satisfied. However, from the viewpoint of further improving the cycle characteristics, the value of the single particle ratio R1 is preferably 80% by volume or more and 100% by volume or less, more preferably 90% by volume or more and 100% by volume or less, even more preferably 95% by volume or more and 100% by volume or less, and particularly preferably 100% by volume (i.e., all of the positive electrode active material contained in the first surface layer is single particle). In addition, from the viewpoint of further improving the rate characteristics, the value of the single particle ratio R2 is preferably 0% by volume or more and 20% by volume or less, more preferably 0% by volume or more and 10% by volume or less, even more preferably 0% by volume or more and 5% by volume or less, and particularly preferably 0% by volume (i.e., all of the positive electrode active material contained in the second surface layer is polycrystalline). From the viewpoint of further improving the rate characteristics and cycle characteristics, it is preferable that the single particle ratio R1 is 80 volume % or more and 100 volume % or less, and the single particle ratio R2 is 0 volume % or more and 20 volume % or less. More preferably, the single particle ratio R1 is 90 volume % or more and 100 volume % or less, and the single particle ratio R2 is 0 volume % or more and 10 volume % or less. Even more preferably, the single particle ratio R1 is 95 volume % or more and 100 volume % or less, and the single particle ratio R2 is 0 volume % or more and 5 volume % or less. Particularly preferably, the single particle ratio R1 is 100 volume % and the single particle ratio R2 is 0 volume %.

[0039] The manufacturing method of the positive electrode active material layer having the above-mentioned configuration is not particularly limited. For example, the positive electrode active material layer can be manufactured by separately manufacturing a first positive electrode active material layer made using a positive electrode active material with a high ratio of single particles and a second positive electrode active material layer made using a positive electrode active material with a low ratio of single particles (high ratio of polycrystals), and laminating them. Then, when assembling the battery, the positive electrode active material layer made of the laminate is arranged so that the first positive electrode active material layer is located on the solid electrolyte layer side and the second positive electrode active material layer is located on the positive electrode current collector side, thereby manufacturing the all-solid-state battery according to this embodiment.

[0040] The shape of the positive electrode active material may be, for example, particulate (spherical, fibrous) or the like. When the positive electrode active material is particulate, the average particle diameter is, for example, preferably within the range of 1 nm to 100 μm, more preferably within the range of 10 nm to 50 μm, further preferably within the range of 100 nm to 20 μm, and particularly preferably within the range of 1 to 20 μm. In this specification, the term "particle diameter" refers to the maximum distance between any two points on the contour line of a particle observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM). In addition, the value of "average particle diameter" refers to the arithmetic mean value of the "particle diameter".

[0041] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably more than 50% by mass, more preferably more than 50% by mass to 95% by mass, and even more preferably 60% by mass to 90% by mass, based on 100% by volume of the total solid content in the positive electrode active material layer. The content of the positive electrode active material in the positive electrode active material layer is preferably more than 30% by volume, more preferably more than 40% by volume to 80% by volume, and even more preferably 50% by volume to 70% by volume, based on 100% by volume of the total solid content in the positive electrode active material layer.

[0042] The positive electrode active material layer preferably further contains a solid electrolyte. The positive electrode active material layer contains a solid electrolyte, which can improve the ionic conductivity of the positive electrode active material layer. There is no particular restriction on the specific form of the solid electrolyte contained in the positive electrode active material layer, and the solid electrolytes and their preferred forms exemplified in the section on the negative electrode active material layer can be similarly adopted. The content of the solid electrolyte in the positive electrode active material layer is preferably 1% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and even more preferably 10% by mass or more and 30% by mass or less, based on 100% by volume of the total solid content contained in the positive electrode active material layer. The content of the solid electrolyte in the positive electrode active material layer is preferably 1% by volume or more and 50% by volume or less, more preferably 5% by volume or more and 45% by volume or less, and even more preferably 10% by volume or more and 30% by volume or less, based on 100% by volume of the total solid content contained in the positive electrode active material layer. If the content of the solid electrolyte in the positive electrode active material layer is within the above range, the ionic conductivity and energy density of the positive electrode active material layer can be compatible.

[0043] In the case where the positive electrode active material layer contains a solid electrolyte, the content ratio of the solid electrolyte to 100% by mass of the total solid content contained in the first surface layer is preferably higher than the content ratio of the solid electrolyte to 100% by mass of the total solid content contained in the second surface layer. Since the surface area per unit volume of a single particle positive electrode active material is smaller than that of a polycrystalline positive electrode active material, the ion conductivity can be improved by increasing the proportion of the solid electrolyte in the first surface layer having a high single particle ratio. In particular, when the amount of solid electrolyte in the positive electrode active material layer is constant, it is possible to achieve not only high cycle characteristics but also improvement in rate characteristics by increasing the proportion of the solid electrolyte in the first surface layer having a high single particle ratio compared to that in the second surface layer, rather than dispersing the solid electrolyte uniformly throughout the positive electrode active material layer.

[0044] Moreover, the positive electrode active material layer may further contain at least one of a binder and a conductive assistant, in addition to the above-mentioned positive electrode active material and solid electrolyte.

[0045] The thickness of the positive electrode active material layer differs depending on the intended configuration of the secondary battery, but is preferably within the range of, for example, 0.1 to 1000 μm, and more preferably 40 to 100 μm.

[0046] As described above, the positive electrode active material layer is formed by laminating a first positive electrode active material layer made of a positive electrode active material having a high ratio of single particles and a second positive electrode active material layer made of a positive electrode active material having a low ratio of single particles (a high ratio of polycrystals) (when assembling the battery, the positive electrode active material layer made of the laminate is preferably arranged so that the first positive electrode active material layer is located on the solid electrolyte layer side and the second positive electrode active material layer is located on the positive electrode current collector side). In this case, the thickness of the first positive electrode active material layer is preferably more than 50% of the thickness of the positive electrode active material layer, more preferably more than 50% and 80% or less, and even more preferably 55% or more and 75% or less (the thickness of the second positive electrode active material layer is preferably less than 50% of the thickness of the positive electrode active material layer, more preferably 20% or more and less than 50%, and even more preferably 25% or more and 45% or less). In this case, the ratio of the single particles in the first positive electrode active material layer is preferably 80% by volume or more and 100% by volume or less, more preferably 90% by volume or more and 100% by volume or less, even more preferably 95% by volume or more and 100% by volume or less, and particularly preferably 100% by volume (i.e., all of the positive electrode active material contained in the first positive electrode active material layer is single particles). In addition, the ratio of the single particles in the second positive electrode active material layer is preferably 0% by volume or more and 20% by volume or less, more preferably 0% by volume or more and 10% by volume or less, even more preferably 0% by volume or more and 5% by volume or less, and particularly preferably 0% by volume (i.e., all of the positive electrode active material contained in the second surface layer is polycrystalline). By adopting such a configuration, the cycle characteristics can be further improved. In this specification, the "ratio of single particles in the first positive electrode active material layer" and the "ratio of single particles in the second positive electrode active material layer" can be determined in accordance with <Measurement of single particle ratios (R1 and R2)> in the Examples described later (i.e., by measuring in the same manner except that the measurement targets are changed from the "first surface layer" and "second surface layer" to the "first positive electrode active material layer" and "second positive electrode active material layer").

[0047] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 27 and the negative electrode current collector plate 25 may be made of the same material or different materials.

[0048] [Positive and negative leads] Although not shown in the figure, the current collector and the current collector plate may be electrically connected via a positive electrode lead and a negative electrode lead. As the constituent materials of the positive electrode and the negative electrode lead, materials used in known secondary batteries may be similarly adopted. Note that the part taken out from the exterior is preferably covered with a heat-resistant insulating heat shrink tube or the like so as not to come into contact with peripheral devices or wiring, causing leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).

[0049] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in Figs. 1 and 2, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.

[0050] The stacked secondary battery according to the present embodiment has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has high capacity and excellent cycle durability, and is therefore suitable for use as a driving power source for EVs and HEVs.

[0051] The following embodiments are also included within the scope of the present invention: an all-solid-state battery according to claim 1 having the features of claim 2; an all-solid-state battery according to claim 2 having the features of claim 3; an all-solid-state battery according to any one of claims 1 to 3 having the features of claim 4. EXAMPLES

[0052] The present invention will be described in more detail below with reference to examples. However, the technical scope of the present invention is not limited to the following examples. In the following, the tools and devices used in the glove box were thoroughly dried in advance.

[0053] <Example of evaluation cell preparation> [Example 1] (Preparation of Positive Electrode Active Material Layer) (1) Preparation of positive electrode active material layer (single particle, thickness 50 μm) As a constituent material of the positive electrode active material layer, single particle NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1O2, average particle diameter: 4.0 μm), an argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle diameter (D50): 0.2 μm) as a solid electrolyte, carbon nanofiber (CNF) (manufactured by Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150 nm, average fiber length: about 9 μm) as a conductive assistant, and polytetrafluoroethylene (PTFE) as a binder were prepared. In a glove box in an argon atmosphere with a dew point of -68 ° C or less, the positive electrode active material, the solid electrolyte, the conductive assistant, and PTFE were weighed to a volume ratio of 61.2: 31.5: 3.9: 3.4, and kneaded in an agate mortar. After confirming that the binder was fibrillated, the obtained powder composition was supplied to a powder inlet set in a roll press machine. The powder composition was then rolled using a roll press (conditions are shown below) to form the powder composition into a sheet. The resulting sheet was folded in half, and the folded sheet was again rolled using a roll press (conditions are shown below) (folding and rolling). The folding and rolling was repeated three times to obtain a sheet, which was then punched out into a circle with a diameter of 19 mm to obtain a positive electrode active material layer (single particle, thickness 50 μm).

[0054] (Roll press machine conditions) Roll size: 250mmφ×400mm Roll speed: 1m / min Roll gap: 50μm Pressure: 10kN (Linear pressure: 25kN / m).

[0055] (2) Preparation of positive electrode active material layer (polycrystalline, 50 μm thick) Instead of single-particle NMC composite oxide, polycrystalline NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 A positive electrode active material layer (polycrystalline, thickness 50 μm) was obtained in the same manner as described above (Preparation of positive electrode active material layer (single particle)), except that O2 (average particle diameter: 4.0 μm, primary particle diameter: 300 nm or less) was used as the positive electrode active material.

[0056] (Preparation of solid electrolyte layer) In a glove box with an argon atmosphere having a dew point of -68°C or less, 95 parts by mass of an argyrodite-type sulfide solid electrolyte (Li6PS5Cl) as a solid electrolyte and a binder solution (5 parts by mass of styrene-butadiene rubber (SBR) as a binder dissolved in mesitylene as a solvent) were mixed to prepare a solid electrolyte slurry. The obtained solid electrolyte slurry was applied to the surface of a stainless steel foil as a support using an applicator, dried, and then punched out into a circle with a diameter of 25 mm to obtain a solid electrolyte layer with a thickness of 40 μm.

[0057] (Preparation of evaluation cells) In a glove box in an argon atmosphere with a dew point of -68°C or less, the above-prepared positive electrode active material layer (polycrystalline, 50 μm thick) and the positive electrode active material layer (single particle, 50 μm thick) were stacked in this order on an aluminum foil (circular, 19 mm diameter) as a positive electrode current collector. Then, the above-prepared solid electrolyte layer formed on the stainless steel foil surface was stacked on the positive electrode active material layer (single particle, 50 μm thick) so that the exposed surface of the solid electrolyte layer faces the positive electrode active material layer (single particle, 50 μm thick), and the solid electrolyte layer was transferred onto the positive electrode active material layer (single particle, 50 μm thick) by cold isostatic pressing (CIP). After peeling off the stainless steel foil adjacent to the solid electrolyte layer, the stainless steel foil (circular, 19 mm diameter) as a negative electrode current collector was stacked and pressed by cold isostatic pressing (CIP) to prepare a laminate. An aluminum positive electrode tab and a nickel negative electrode tab were bonded to an aluminum foil as a positive electrode current collector and a stainless steel foil as a negative electrode current collector, respectively, by an ultrasonic welding machine, and the resulting laminate was placed inside an aluminum laminate film and vacuum sealed to obtain an evaluation cell of this example (lithium precipitation type all-solid-state lithium secondary battery).

[0058] [Comparative Example 1] (Preparation of Positive Electrode Active Material Layer) As a constituent material of the positive electrode active material layer, single particle NMC composite oxide (LiNi 0.8 Mn 0.1 Co0.1 O2, average particle diameter: 4.0 μm), an argyrodite-type sulfide solid electrolyte (Li6PS5Cl, average particle diameter (D50): 0.2 μm) as a solid electrolyte, carbon nanofiber (CNF) (manufactured by Showa Denko K.K., VGCF (registered trademark), aspect ratio: 60, average fiber diameter: about 150 nm, average fiber length: about 9 μm) as a conductive assistant, and polytetrafluoroethylene (PTFE) as a binder were prepared. In a glove box in an argon atmosphere with a dew point of -68 ° C or less, the positive electrode active material, the solid electrolyte, the conductive assistant, and PTFE were weighed to a volume ratio of 61.2: 31.5: 3.9: 3.4, and kneaded in an agate mortar. After confirming that the binder was fibrillated, the obtained powder composition was supplied to a powder inlet set in a roll press machine. The powder composition was then rolled using a roll press (conditions are shown below) to form the powder composition into a sheet. The resulting sheet was folded in half, and the folded sheet was rolled again using a roll press (conditions are shown below) (folding and rolling). The folding and rolling was repeated three times to obtain a sheet, which was then punched out into a circle with a diameter of 19 mm to obtain a positive electrode active material layer (single particle, 100 μm thick).

[0059] (Roll press machine conditions) Roll size: 250mmφ×400mm Roll speed: 1m / min Roll gap: 100μm Pressure: 10kN (Linear pressure: 25kN / m).

[0060] (Preparation of solid electrolyte layer) A solid electrolyte layer was produced in the same manner as in Example 1 above.

[0061] (Preparation of evaluation cells) In a glove box in an argon atmosphere with a dew point of -68°C or less, the positive electrode active material layer (single particle, thickness 100 μm) prepared above was stacked on an aluminum foil (circular with a diameter of 19 mm) as a positive electrode current collector. Then, the solid electrolyte layer formed on the stainless steel foil surface prepared above was stacked on the positive electrode active material layer so that the exposed surface of the solid electrolyte layer faces the positive electrode active material layer, and the solid electrolyte layer was transferred onto the positive electrode active material layer by cold isostatic pressing (CIP). After peeling off the stainless steel foil adjacent to the solid electrolyte layer, a stainless steel foil (circular with a diameter of 19 mm) was stacked as a negative electrode current collector, and pressed by cold isostatic pressing (CIP) to prepare a laminate. An aluminum positive electrode tab and a nickel negative electrode tab were bonded to the aluminum foil as a positive electrode current collector and the stainless steel foil as a negative electrode current collector, respectively, by an ultrasonic welding machine, and the obtained laminate was placed inside an aluminum laminate film and vacuum sealed to obtain an evaluation cell (lithium precipitation type all-solid-state lithium secondary battery) of this comparative example.

[0062] [Comparative Example 2] In the above (preparation of the positive electrode active material layer), single-particle NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, average particle size: 4.0 μm) was replaced with polycrystalline NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 An evaluation cell for this comparative example (a lithium precipitation-type all-solid-state lithium secondary battery) was obtained in the same manner as in Comparative Example 1, except that a positive electrode active material (CuO2, average particle diameter: 4.0 μm, primary particle diameter: 300 nm or less) was used as the positive electrode active material.

[0063] [Comparative Example 3] In the above (preparation of the positive electrode active material layer), single-particle NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2, average particle size: 4.0 μm) and polycrystalline NMC composite oxide (LiNi 0.8 Mn 0.1 Co 0.1A cell for evaluation of this comparative example (a lithium precipitation-type all-solid-state lithium secondary battery) was obtained in the same manner as in Comparative Example 1, except that a mixture containing equal volumes of ZnO, ZnSe, and ZnSe (average particle size: 4.0 μm, primary particle size: 300 nm or less) was used as the positive electrode active material.

[0064] [Comparative Example 4] An evaluation cell of this comparative example (lithium precipitation type all-solid-state lithium secondary battery) was obtained in the same manner as in Example 1, except that the following method was used instead of the above (production of evaluation cell).

[0065] (Preparation of evaluation cells) In a glove box in an argon atmosphere with a dew point of -68°C or less, the above-prepared positive electrode active material layer (single particle, 50 μm thick) and the positive electrode active material layer (polycrystalline, 50 μm thick) were stacked in this order on an aluminum foil (circular, 19 mm diameter) as a positive electrode current collector. Then, the above-prepared solid electrolyte layer formed on the stainless steel foil surface was stacked on the positive electrode active material layer (polycrystalline, 50 μm thick) so that the exposed surface of the solid electrolyte layer faces the positive electrode active material layer (polycrystalline, 50 μm thick), and the solid electrolyte layer was transferred onto the positive electrode active material layer (polycrystalline, 50 μm thick) by cold isostatic pressing (CIP). After peeling off the stainless steel foil adjacent to the solid electrolyte layer, the stainless steel foil (circular, 19 mm diameter) as a negative electrode current collector was stacked and pressed by cold isostatic pressing (CIP) to prepare a laminate. An aluminum positive electrode tab and a nickel negative electrode tab were bonded to an aluminum foil as a positive electrode collector and a stainless steel foil as a negative electrode collector, respectively, using an ultrasonic welding machine, and the resulting laminate was placed inside an aluminum laminate film and vacuum sealed to obtain an evaluation cell for this comparative example (a lithium precipitation-type all-solid-state lithium secondary battery).

[0066] <Measurement of single particle ratio (R1 and R2)> For the evaluation cells prepared in the above examples and comparative examples, the single particle ratios (R1 and R2) of the first and second surface layers in the positive electrode active material layer were measured by crystal analysis using SEM-EBSD (scanning electron microscope-electron backscattering analysis). First, the evaluation cell was disassembled, and the positive electrode active material layer was cut in the thickness direction by FIB (focused ion beam) processing to expose the cross section. The first surface layer (up to a thickness of 20% (20 μm) from the surface facing the solid electrolyte layer) was observed in 10 fields of view, and a crystal orientation map for the first surface layer was obtained for 10 fields of view by crystal analysis using SEM-EBSD. Next, from the crystal orientation map, it was determined whether or not a grain boundary was observed for each particle of the positive electrode active material. Those in which a grain boundary was observed (crystals with different crystal orientations were observed inside the outline of the positive electrode active material particle) were classified as "polycrystalline", and those in which a grain boundary was not observed (positive electrode active material particles consisted only of crystals with a single crystal orientation) were classified as "single particle". Furthermore, the particle diameters of each particle of the positive electrode active material present in the 10 visual fields were determined, and their arithmetic average value was defined as the average particle diameter d1 (μm) of the positive electrode active material. Furthermore, the particle diameters of each single particle present in the 10 visual fields were determined, and their arithmetic average value was defined as the average particle diameter d2 (μm) of the single particle. Then, the single particle ratio R1 (volume %), which is the ratio of the total volume of the single particles to the total volume of the positive electrode active material contained in the first surface layer, was calculated from the following formula I. Similarly, the second surface layer (up to 20% (20 μm) thickness from the surface facing the positive electrode current collector) was observed in 10 fields of view, and a crystal orientation map for the second surface layer was obtained for the 10 fields of view by crystal analysis using SEM-EBSD. Next, from the crystal orientation map, it was determined whether or not a crystal grain boundary was observed for each particle of the positive electrode active material, and those in which a crystal grain boundary was observed (crystals with different crystal orientations were observed inside the outline of the positive electrode active material particle) were classified as "polycrystalline", and those in which a crystal grain boundary was not observed (positive electrode active material particles consisted only of crystals with a single crystal orientation) were classified as "single particle". Furthermore, the particle diameter of each particle of the positive electrode active material present in the 10 fields of view was obtained, and the arithmetic average value of these was used as the average particle diameter d3 (μm) of the positive electrode active material. In addition, the particle diameter of each single particle present in the 10 fields of view was obtained, and the arithmetic average value of these was used as the average particle diameter d4 (μm) of the single particle.Then, the single particle ratio R2 (volume %), which is the ratio of the total volume of the single particles to the total volume of the positive electrode active material contained in the second surface layer, was calculated from the following formula II. The obtained single particle ratios (R1 and R2) are shown in Table 1 below.

[0067]

number

[0068] <Evaluation of rate characteristics> A pressure of 3 MPa was applied to the evaluation cell in the stacking direction using a pressure member. In this state, the upper and lower limit voltages were set to 2.5 to 4.3 V under a temperature condition of 25°C, and a current of 0.45 mA / cm 2 and 15.6mA / cm 2 CC charging and discharging was performed at a current value of 0.45mA / cm and the charge capacity was measured at each current value. 2 Charge capacity at a current value of 15.6mA / cm 2 The rate characteristic was evaluated from the percentage of the charge capacity at the current value (charge capacity ratio). The higher the charge capacity ratio, the better the rate characteristic. The results are shown in Table 1 below.

[0069] <Evaluation of cycle characteristics> A pressure of 3 MPa was applied to the evaluation cell in the stacking direction using a pressure member. In this state, the upper and lower limit voltages were set to 2.5 to 4.3 V under a temperature condition of 25°C, and a current of 2.25 mA / cm 2 CC charge and discharge was repeated 200 cycles at a current value of 1000 mA. The ratio of the discharge capacity at the 200th cycle to the initial discharge capacity was calculated as a percentage (discharge capacity retention rate), and the cycle characteristics were evaluated from this value. A higher discharge capacity retention rate indicates better cycle characteristics. The results are shown in Table 1 below.

[0070] [Table 1]

[0071] As shown in Table 1, it is understood that the all-solid-state battery according to the present invention can achieve both rate characteristics and cycle characteristics. [Explanation of symbols]

[0072] 10a laminated secondary battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film.

Claims

1. a positive electrode having a positive electrode active material layer containing a positive electrode active material disposed on a surface of a positive electrode current collector; A negative electrode; a solid electrolyte layer interposed between the positive electrode and the negative electrode and containing a solid electrolyte; An all-solid-state battery having a power generating element having In the positive electrode active material layer, a single particle ratio R is a ratio of the total volume of single particles to the total volume of the positive electrode active material contained in a first surface layer up to a thickness of 20% from the surface facing the solid electrolyte layer. 1 (volume %) is the ratio of the total volume of single particles to the total volume of the positive electrode active material contained in the second surface layer up to 20% thickness from the surface facing the positive electrode current collector. 2 (Volume %) is larger than that of an all-solid-state battery.

2. The all-solid-state battery according to claim 1 , wherein the positive electrode active material is a composite oxide containing lithium and nickel.

3. The positive electrode active material is represented by the following general formula (1): Li a Ni b Mn c Co d M x O 2 (1) In the formula, a, b, c, d, and x satisfy 0.98≦a≦1.2, 0.8≦b≦0.9, 0<c≦0.2, 0<d≦0.2, 0≦x≦0.2, and b+c+d+x=1; and M is at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, and Cr. The all-solid-state battery according to claim 2 , wherein the composite oxide has a composition represented by the formula:

4. The single particle ratio R 1 is 90% by volume or more and 100% by volume or less, and the single particle ratio R 2 The all-solid-state battery according to claim 1 or 2, wherein the volume percentage of the at least one of the first and second electrodes is 0% or more and 10% or less by volume.

Citation Information

Patent Citations

  • Mobile telephone system

    JP1988014563A

Cited By

  • Battery cell

    CN122739363A

  • battery cell

    JP2026148958A